Consumption, production, inflation and interest rates - Breeden, Douglas T. (Journal of Financial Economics, 1986)
This paper uses discrete-time and continuous-time models to derive equilibrium relations among real and nominal interest rates and the expected growth, variance and covariance parameters of optimally chosen paths for aggregate real consumption and aggregate production. Simple, intuitive and fairly general relations are obtained which apply to most of the models of financial economics of the past 20 years. The single-good analysis generalizes and provides a synthesis of many prior works, whereas the multi-good analysis provides more original results. Consistent business cycle movements are examined for interest rates, inflation and consumption and production aggregates.